The Effects of rs405509 on APOEε4 Non-carriers in Non-demented Aging - Wu, Dongpeng; Zhao, Han; Gu, Huali; Han, Bin; Wang, Qingqing; Man, Xu; Zhao, Renliang; Liu, Xuejun; Sun, Jinping (Frontiers in Neuroscience, 2021)
Background: There is evidence that the T allele of rs405509 located in the apolipoprotein E (APOE) promotor region is a risk factor for Alzheimer's disease (AD). However, the effect of the T/T allele on brain function in non-demented aging is still unclear. Methods: We analyzed the effects of the rs405509 T/T allele on cognitive performances using multiple neuropsychological tests and local brain function using resting-state functional magnetic resonance imaging (rs-fMRI). Results: Significant differences were found between T/T carriers and G allele carriers on general cognitive status, memory, and attention (p<0.05). Rs-fMRI analyses demonstrated decreased amplitude of low frequency fluctuation (ALFF) in the right middle frontal gyrus, decreased percent amplitude of fluctuation (PerAF) in the right middle frontal gyrus, increased regional homogeneity (ReHo) in the right cerebellar tonsil and decreased ReHo in the right putamen, and decreased degree centrality (DC) in the left middle frontal gyrus (p < 0.05, corrected). Furthermore, significant correlations were found between cognitive performance and these neuroimaging changes (p<0.05). Conclusion: These findings suggest that T/T allele may serve as an independent risk factor that can influence brain function in different regions in non-demented aging.